Getting globalization right : the dilemmas of inequality - Tulchin, Joseph S.(ed.); Bland, Gary (ed.) (New Delhi, 2007)
The authors argue that, without effective national policies to dampen the effects of globalization, the short-term impact of opening the economy has a negative effect on levels of poverty and inequality. In a more positive vein, however, and without minimizing the difficulties involved, they identify the types of social policies that can blunt or counter these negative effects. They also suggest that international governance will have a growing influence on how globalization affects individual nations.
Keywords: Economic development